PELATIHAN PEMBUATAN DETERGEN CAIR BERBASIS AROMA TERAPI SERAI WANGI DENGAN TEKNOLOGI MIXER BOR - Makhroji Makhroji; Siska Rita Mahyuny; Nursamsu Nursamsu (Politeknik Negeri Sriwijaya, 2022)
The community service activity program given to partners is in the form of training in the manufacture of aromatherapy-based liquid detergent with drill mixer technology. In the process of this activity, participants will be given a drill mixer as a technology stirrer that produces large amounts of liquid detergent. The process of this activity is also the community service team providing knowledge of the product marketing process that has been made as a group business. The basis of the goal of the community service team to select the Ms. PKK group in Matang Teupah Village, Bendahara District, Aceh Tamiang Regency is that the PKK group has the potential to advance the group, but they are limited in knowledge and funds to start from where to start a business and make products as income. economics for groups. Thus, this service activity was precisely carried out, the proof of this that the service team obtained it was seen by the enthusiasm of Mrs. PKK in Matang Teupah Village who attended the training activity and they were also enthusiastic to help the service team in the process of making liquid detergent. We use the results of this activity as data in distributing an understanding questionnaire which will be evidence that the sustainability of service activities will be carried out next. The results obtained from the questionnaire understanding of 89% on the indicators of knowledge of product-making materials, it can be concluded that service activities have a positive impact on the PKK group.